Treatment of hypopharyngeal carcinoma complicated with diabetic nephropathy: a case report and literature review - Liu, Wei; Peng, Jin-Fu; Tang, Meng-Jie (Translational Cancer Research; Vol 9, No 3 (March 31, 2020): Translational Cancer Research, 2020)
For elderly cancer patients with diabetic nephropathy, severe renal insufficiency leads to a very high risk of chemotherapy. Physicians and pharmacists must consider both the benefits of cancer treatment and the impact of antineoplastic drugs on patients’ residual renal function, and choose appropriate chemotherapy regimens to balance the efficacy and safety of drugs. We report a case of a patient who presented with dysphagia and sore throat with serum creatinine of 169 μmol/L and fasting blood glucose of 7.9 mmol/L on admission. The main diagnosis was hypopharyngeal carcinoma with diabetic nephropathy. The clinical pharmacist reviewed the literature and analyzed the pharmacological and pharmacokinetic characteristics of anti-tumor drugs in patients, and adjusted the chemotherapy regimen and dose according to the renal function of patients. To the best of our knowledge, this is the first reported case of hypopharyngeal carcinoma with severe renal insufficiency treated successfully with multimodality therapy in China. The purpose of this case is to optimize the anti-tumor treatment regimen and drug dose adjustment of hypopharyngeal carcinoma with severe renal insufficiency, so as to provide a reference for clinicians and clinical pharmacists to use drugs rationally.